The Impact of climate risk on the profitability of mango (Mangifera indica) cultivation in Chilaco-Lancones using Monte Carlo simulation - Bazan Hidalgo, Antonella Isabel (2026)
Climate change is having a significant impact on tropical agriculture, affecting the profitability of mango (Mangifera indica) cultivation in Sullana, Peru. The objective was to estimate the economic impact of climate risk on mango producers in Chilaco-Lancones using Monte Carlo simulation. A non-experimental design and a mixed-methods approach were applied, analyzing climate data from 2023–2024 and records from 12 local farmers. The results revealed that temperature, precipitation, and humidity directly affect productivity. Furthermore, the simulations show losses of S/.22,958.77 in the Normal scenario and S/.68,306.75 in the Warm-Dry scenario, while the Humid-Cold scenario generated gains of S/.22,321.44. Therefore, Monte Carlo simulation allowed for the assessment of economic vulnerability and the strengthening of agricultural resilience among mango producers in Chilaco-Lancones.